Decorations of the boqta and their symbolic meanings (Mongolian Journal of Arts and Culture, 2023)
The hat, which has the most unique design and rich decoration Among the Mongolian hats from the time of the Mongol Empire is the wife`s hat Boqta. The article considers boqta hats of Mongol women in the 13th-14th centuries, comparing the written and pictorial sources and the actual finds found in archaeological excavations to determine the validity and diversity of the research subject. According to research it is clear that the decoration of boqta hats was too many kinds. In addition to being beautiful, these various decorations had a deep symbolic meaning. Also, it represented the status of social class, wealth, and religion of the wearer. With the expansion of the empire, the decoration of the boqta evolved and the craftsmanship became more elaborate due to the mutual influence of the culture, customs, religion, and wealth of the other countries occupied by empire. Therefore, on the other hand, thedecoration of the boqta hat indicated the extent and reach of the Mongol empire.Богтаг малгайн чимэглэлүүд, тэдгээрийн бэлгэдэлХураангуй: Монгол ын эзэнт гүрний үеийн монгол малгайн уудаас ха мгийн өвөрмөц хийц маяг, баялаг чимэгл элтэй нь эхнэр хүний богтаг малгай юм. Уг нийтл элд археологийн малтлагаар олдсон болон зургийн, бичгийн сурвал жууд дахь XIII-XIV зууны үеийн монгол эмэгтэйн богтаг малгайг хар ьцуулан судалсн ы үндсэн дээр судалгаан ы сэдвийн үндэслэл, олон талт байдлыг тодорхойлох болно . Судалгаанаас үзэхэд, богтаг малгайн чимэгл эл нь маш олон янзын хийц хэлбэрт эй байсан нь тодорхой байна. Тэдгээр олон янзын чимэгл элүүд нь го ё сайхан харагдах талаасаа гадна бэлгэдлийн нарийн утгыг агуулдаг байв. Түүнчлэн өмсөж буй эзнийхээ зэрэг зиндаа, хөрөнгө чинээ, шашин шүтл эгийг хүрт эл илэрхийлдэг байжээ. Эзэнт гүрэн өргөжин тэлэхийн хирээр эзлэн суусан бусад орнуудын соёл, ёс заншил, шашин шүтл эг, эд баялаг зэрэг хүчин зүйлсийн харил цан нөлөөгөөр богтагн ы чимэгл элийн материал , хэлбэр, ур хийц, утга бэлгэдэл хувьсан өөрчлөгд өж байсан байна.Түлхүүр үгс: өд, оройн чимэг, сувд, цог чимэг, ом үсэг